Presidential Elections in the Republic of Turkey in the Information Space of the Balkan Countries: Media Geographical Analysis - Arina A. Mulina; Tamara S. Yakova (RUDN Journal of Studies in Literature and Journalism)
Presents the results of a study of the information space of the Balkan states conducted during the presidential elections in Turkey in 2023. The authors referred to this period as one of the most striking political events in the country over the past five years. The purpose of the proposed work is to identify the level of interest in Turkey’s domestic political events both from residents of the Balkan countries and from the national media of Serbia, Croatia, Bosnia and Herzegovina, as well as to compare the data obtained and identify a correlation between them. It is hypothesized that the inhabitants of the Balkan states pay great attention to the issues of Turkey’s foreign and domestic policy. The level of interest of residents of these states is revealed based on the analysis of big data in the spatial-temporal coordinate system (media geographic approach). Ranking and media metric analysis made it possible to trace the dynamics of changes in the number of requests on the topics Turkey and Recep Tayyip Erdogan (the main markers of the presidential race). The results of the second stage of the study (content analysis of publications of the national mass media of Serbia, Croatia and Bosnia and Herzegovina) allowed us to compare the results of the two stages of the analysis. The authors conclude that Internet users of the Balkan states did not show significant interest in the political life of the Republic of Turkey and considered the country more as a place for tourism and recreation, while the national media of this region turned much more often to the political life of Turkey than to other topics.